Sex Differences in Physiological Acclimatization after Transfer in Wistar Rats - Johanna W. M. Arts; Klaas Kramer; Saskia S. Arndt; Frauke Ohl (Animals, 2014)
Most laboratory animals used in research are vendor-bred and transferred to research facilities. Transfer procedures might have considerable and unintended effects on research results. In the present study we compared physiological and behavioral parameters before and after external and internal transfer, as well as between transferred and non-transferred Wistar rats. The impact of both external and internal transfer on body weight, plasma corticosterone levels, heart rate, blood pressure, and locomotor activity was studied in both male and female Wistar rats, taking into account the sex differences in stress responsivity. External transfer was found to decrease body weight, increase plasma corticosterone, increase activity, increase heart rate in female rats, but decrease heart rate in male rats. Parameters showed differences between the sexes and light phases. This study shows that acclimatization after transfer is sex-specific and researchers should take the sex into consideration when determining the acclimatization period. It is recommended to allow for acclimatization of at least 8 days in males and two weeks in females after external transfer and timely (2 days before starting experiments) transfer the animals internally to the testing room.